2004
DOI: 10.1128/jb.186.21.7411-7419.2004
|View full text |Cite
|
Sign up to set email alerts
|

Use of In Vivo Expression Technology To Identify Genes Important in Growth and Survival of Pseudomonas fluorescens Pf0-1 in Soil: Discovery of Expressed Sequences with Novel Genetic Organization

Abstract: Studies were undertaken to determine the genetic needs for the survival of Pseudomonas fluorescens Pf0-1, a gram-negative soil bacterium potentially important for biocontrol and bioremediation, in soil. In vivo expression technology (IVET) identified 22 genes with elevated expression in soil relative to laboratory media. Soil-induced sequences included genes with probable functions of nutrient acquisition and use, and of gene regulation. Ten sequences, lacking similarity to known genes, overlapped divergent kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 43 publications
(34 reference statements)
1
105
0
Order By: Relevance
“…Lugtenberg and Dekkers (21) have shown that utilization of organic acids by P. fluorescens is the nutritional basis governing the ability of this organism to colonize tomato roots. Genes in pseudomonads encoding proteins with functions in nutrient acquisition and in energy generation are up-regulated in the rhizosphere or when bacteria were exposed to the soil environment as revealed by in vivo expression technology-based approaches (22,23). Differences in expression of these genes in response to the var.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lugtenberg and Dekkers (21) have shown that utilization of organic acids by P. fluorescens is the nutritional basis governing the ability of this organism to colonize tomato roots. Genes in pseudomonads encoding proteins with functions in nutrient acquisition and in energy generation are up-regulated in the rhizosphere or when bacteria were exposed to the soil environment as revealed by in vivo expression technology-based approaches (22,23). Differences in expression of these genes in response to the var.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo expression technology is now established as a method of analyzing bacterial gene expression in the rhizosphere as an approach for the identification of genes involved in microbe-plant interactions (22,23,29,35). One clear advantage of in vivo expression technology is that investigations are carried out in the appropriate environment in the organism of interest; there is no extrapolation from in vitro model systems.…”
Section: Evaluation and Comparison With Other Techniques To Study Rhizo-mentioning
confidence: 99%
“…Mutants were constructed using the gene splicing by overlap extension method (48) and homologous recombination as previously outlined (49). Primers complimentary to regions flanking the targeted gene were used to monitor the proper replacement with the mutant constructs by PCR, and confirmed by sequencing both template strands.…”
Section: Methodsmentioning
confidence: 99%
“…Genes were deleted from the P. fluorescens Pf0-1 genome by SOE-PCR (Horton et al, 1989) and allele exchange using suicide plasmid pSR47s (Matthews and Roy, 2000) as described previously (Silby and Levy, 2004). Two of the deletion mutants obtained, Pfl01_3463-66 (bases 3947327-3952129) and Pfl01_3655-59 (bases 4136447-4143889), were used for comparison of antibiotic production with the wild-type strain.…”
Section: Extraction Of Antimicrobial Compoundsmentioning
confidence: 99%